Soluciones solitónicas e instantónicas en teorías de Yang-Mills - Benítez, H. A. (2011)
We introduce non-abelian gauge theory in SU(2) group and we study the instanton and the soliton as solutions in the field theory and their correspondence. In these Yang-Mills solutions in the Minkowski and euclidean space we find instantons and monopole behaviour.